2011
DOI: 10.1177/0022022111399649
|View full text |Cite|
|
Sign up to set email alerts
|

Social Class Predicts Generalized Trust But Only in Wealthy Societies

Abstract: This research examined the relationship between social class and generalized trust, or a belief that others have a benign intention in social interactions, in a diverse set of societies represented in the World Values Survey. The strength of the relationship varied significantly across societies: Although social class was a positive predictor of generalized trust in wealthy countries, as reported in past research, among less wealthy countries social class was uncorrelated with trust. These results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 21 publications
3
73
0
3
Order By: Relevance
“…There is a consistent positive correlation between socioeconomic status and social trust (Alesina & La Ferrara, ; Gheorghiu et al., ; Hamamura, ; Henry, ). One explanation for this pattern builds on research from social psychology on social status and stigma (e.g., Goffman, ; Major, Quinton, & McCoy, ).…”
Section: Social Status → Social Trustmentioning
confidence: 93%
See 2 more Smart Citations
“…There is a consistent positive correlation between socioeconomic status and social trust (Alesina & La Ferrara, ; Gheorghiu et al., ; Hamamura, ; Henry, ). One explanation for this pattern builds on research from social psychology on social status and stigma (e.g., Goffman, ; Major, Quinton, & McCoy, ).…”
Section: Social Status → Social Trustmentioning
confidence: 93%
“…On the other hand, higher socioeconomic status may cause greater social trust because people who have high social status are more likely to have more successful professional experiences, greater social capital (Alesina & La Ferrara, ; Shah, ; cf. Brehm & Rahn, ), and other resources that afford them the risks and vulnerabilities of trust (Hamamura, ). Regardless of the reason, these theoretical perspectives predict that low social status is a cause of social distrust (and conversely, that higher status increases trust).…”
Section: Social Status → Social Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive relationship between the levels of social capital and life satisfaction at country level is well documented (Helliwell et al, 2014;Helliwell, 2008). Moreover, cross-sectional analyses in modern affluent societies have found that interpersonal trust is strongly stratified (Hamamura, 2012). A study by Oishi et al (2011) added a temporal perspective to this thesis and found out that the long-term changes in life satisfaction experienced by lower income groups was not explained by changes in household income, but by decreased perceived unfairness and decreased interpersonal trust.…”
Section: Social Indicatorsmentioning
confidence: 92%
“…SERVICIOS PÚBLICOS, DEMOCRACIA Y CLASES MEDIAS EN AMÉRICA LATINA 163 la misma. Se conjugan en la respuesta factores estructurales (imagen institucionalizada del sistema de estratificación, visibilidad del mismo), individuales (personalidad), situacionales (grupos de referencia), históricos-comparados (comparación con el pasado y confianza respecto al futuro, a las probabilidades de progreso y movilidad social) y criterios de distinción personal (Hamamura 2012;Wilkinson y Pickett 2013;Germani 1963) 4 . Pese a las críticas que sobre este indicador se ciernen, su amplia utilización en estudios de valores, formación de opiniones y en la interpretación de comportamientos sociales se fundamenta en la correlación que guarda el mismo con indicadores objetivos 4.…”
Section: Introductionunclassified